Assessing development strategies to achieve the MDGs in Asia: Macroeconomic strategies of MDG achievement in the Kyrgyz Republic - Roman Mogilevsky; Anarkul Omorova (Center for Social and Economic Research (CASE), 2011)
The paper aims at analyzing macroeconomic and financial strategies, which are to ensure achievement of the Millennium Development Goals (MDGs) in the Kyrgyz Republic. The paper is based on results of simulations generated through the application of standard MAMS, a computable general equilibrium model adjusted to the country situation and calibrated with data of Kyrgyzstan. MAMS-model-based simulation results indicate that a continuation of the current policies under the baseline scenario would allow for achieving MDG1 (poverty reduction) only; the country would fall short of the targets for other MDGs. In order to achieve all MDGs, the country needs to increase government spending on MDG-relevant sectors (education, health, water and sanitation) by 7.8-8.1% of GDP per annum in comparison to the baseline scenario. The scenario that combines increased taxes and aid inflows seems to be the most realistic, but it would still require very substantial increases in tax collections and grant aid. The situation is going to be easier, if the economic growth rates 2011-2015 would be higher than 7% per annum. This is possible, if the government would be more successful in implementation of structural reforms, FDI and private domestic investments attraction and mobilization of resources for infrastructure development. Another possible way out is a substantial increase in government spending efficiency allowing for receiving higher social returns for money spent.
Keywords: D58; E61; E62; H50; H51; H52; H54; H6; I1; I2; O11; O15; O53; 330; CGE model; Kyrgyzstan; macroeconomic policies; Millennium Development Goals; Entwicklungsstrategie; Armutsbekämpfung; Wirtschaftspolitik; Millennium Development Goals; Allgemeines Gleichgewicht; Kirgisistan